2001
DOI: 10.1176/appi.ajgp.9.2.113
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Late-Life Depression and Anxiety With Physical Disability: A Review of the Literature and Prospectus for Future Research

Abstract: Depression and anxiety disorders are associated with excess disability. The authors searched the recent geriatric literature for studies associating late-life depression or anxiety with physical disability. Studies showed depression in old age to be an independent risk factor for disability; similarly, disability was found to be a risk factor for depression. Anxiety in late life was also found to be a risk factor for disability, although not necessarily independently of depression. Increased disability due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
260
2
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(281 citation statements)
references
References 0 publications
17
260
2
2
Order By: Relevance
“…Chronic conditions, disability and cognitive decline are very significant determinants of depression among the older old (Lenze et al 2001;Braam et al 2005). Our findings provide firm support for this hypothesis; effects of these predictors remain measurable and very strong in spite of the socio-demographic confounders included in the models.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Chronic conditions, disability and cognitive decline are very significant determinants of depression among the older old (Lenze et al 2001;Braam et al 2005). Our findings provide firm support for this hypothesis; effects of these predictors remain measurable and very strong in spite of the socio-demographic confounders included in the models.…”
Section: Discussionsupporting
confidence: 75%
“…Poor physical health is an important risk factor precipitating poor mental health among older persons (Lenze et al 2001;Yang and George 2005). Braam et al (2005) using data from 14 research groups in 11 European countries (EURODEP consortium) found that suffering from chronic illnesses and functional disabilities was related to higher chances of suffering from depression, even after controlling for age, sex, marital status and education.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is not an isolated illness but also occurs along with other health problems, in particular with physical illness . Poor physical health is an important risk factor for depression in later life (Lenze et al 2001;Braam et al 2005).…”
Section: Other Determinants Of Mental Healthmentioning
confidence: 99%
“…Depression severity is a predictor of variance in instrumental activities of daily living [10]. The mechanisms linking depression and disability are still unclear, but it appears that the depressed state itself can be disabling, and depression increases the disability caused by chronic medical conditions [11]. Bruce and colleagues [12] have described a mutually reinforcing, downward-spiraling relationship between depression and disability.…”
mentioning
confidence: 99%